A supramolecular strategy based on molecular dipole moments for high-quality covalent organic frameworks. Issue 51 (3rd June 2016) - Salonen, Laura M.; Medina, Dana D.; Carbó-Argibay, Enrique; Goesten, Maarten G.; Mafra, Luís; Guldris, Noelia; Rotter, Julian M.; Stroppa, Daniel G.; Rodríguez-Abreu, Carlos
Abstract : Attractive intermolecular interactions of building blocks with strong dipole moments result in a COF with high crystallinity and large surface area. Abstract : A supramolecular strategy based on strong molecular dipole moments is presented to gain access to covalent organic framework structures with high crystallinity and porosity. Antiparallel alignment of the molecules within the pore walls is proposed to lead to reinforced columnar stacking, thus affording a high-quality material. As a proof of principle, a novel pyrene dione building block was prepared and reacted with hexahydroxytriphenylene to form a boronic ester-linked covalent organic framework. We anticipate the strategy presented herein to be valuable for producing highly defined COF structures.